The Use of Facebook in Learn to Write in the Perspective of Students EFL Class - Mauludin, Muhamad Rizqi; Rizal, Daviq (Media Penelitian Pendidikan : Jurnal Penelitian dalam Bidang Pendidikan dan Pengajaran, 2023)
There is a strong need to investigate English as a foreign language (EFL) learners’ perceptions of Facebook as a language-learning environment, as their perceptions that directly influence their language development and achievement have not been examined within the EFL learning context. Thus, this study aims to investigate EFL learners’ perceptions of Facebook as a language learning environment. The sample group of the study consisted of 17 EFL learners at a Walisongo Islamic State University. After administering a background questionnaire and a survey that assessed their perceptions, the frequencies, mean scores, standard deviations were computed. The results showed that Indonesian EFL students perceive Facebook as an environment for communication, interaction, socialization, language learning and cultural interaction. It was recommended that further research should focus on the variables and determinants that may affect their perceptions to understand the theoretical and practical aspects regarding cultural differences.